Genetics of seed protein and oil inherited from "BARC-7" soybean in two F2-derived mapping populations. Issue 6 (2nd November 2022) - Ravelombola, F.; Chen, P.; Vuong, T.; Nguyen, H.; Mian, R.; Acuña, A.; Florez-Palacios, L.; Wu, C.; Harrison, D.; De Oliveira, M.; Winter, J.; Ford, M.; et al.
ABSTRACT: Soybean [ Glycine max (L.) Merr.] seed protein inheritance has been extensively studied; however, genetics of high-protein "BARC-7" soybean are still unknown. In this study, we used 250 F2 -derived lines from each of two soybean populations for quantitative trait loci (QTL) mapping. UA 5814HP, with high-protein content, tracing to BARC-7 as maternal grandfather, was a common parent. Field experiments were conducted using a randomized complete block design with one replication across four environments. Seed protein and oil were quantified using near-infrared (NIR) instrument. Genetic linkage maps were constructed using the Infinium Soy6KSNP Beadchips. QTL analysis was performed using a composite interval mapping method. QTL for protein and oil were identified on chromosomes 6, 13, and 20. The known major QTL on chromosome 20 was not detected, but a novel QTL further downstream on chromosome 20 (only detected in population two) had high-protein alleles inherited from BARC-7-derived parent. Fine mapping efforts are currently ongoing for confirmation of these results.